Evaluadores de artículos caldasia vol. 16 nros. 76-79 (1991)
Acero, Arturo / Acosta Alfredo / Aguirre, C. Jaime / Álvarez, Humberto / Andrade, Gonzalo / Arévalo, Isabel / Barrera, Eduardo / Barriga, Ernesto / Bernal, Amanda / Bernal, Rodrigo / Bulla, / M. Germán / Cadena, Albert  / Cala, Plutarco / Campos Martha / Cogollo, Álvaro / Cuadros, Tomas Chamorro, Clara / Churchill, Steven Díaz, Santiago / Duarte, Martha / Dueñas;Hernando / Duque, Santiago / Fernandez, Jose L. / Forero, Eduardo / Franco, Esperanza / Franco, Pilar / Fuertes, Javier / Galeano, Gloria / Galvis, Germán / Gaviria, Elizabeth / Gaviria, Santiago / Gómez, Marcela / González, Favio  / Hernández, C. Jorge / Idrobo, Jesús / La Marca, Enrique / Linares, Mauricio / Londoño, Concha / Lynch,John / Lozano, Gustavo / Lozano, Nubia / Mora, O. Luis E. / Muñoz, Paulina / Murillo, María T. / Orozco, Clara I. / Palacio, Pablo / Pineda, Fabio / Pinto, N. María / Rangel, Orlando / Restrepo, Rubén / Reyes, Carmen / Rueda, Vicente / Ruiz, Pedro M. / Samper, Cristian / Smith, Ernesto / Stiles, Gary / Tchecliakova, Nadya / Turbay, Luisa F. / Uribe, Jaime / Zenner, Ingerborg / Zuluaga,  Silvio